Análise comparativa dos impactos ambientais na indústria de barrilha: eletrólise versus processo Solvay - Marchezepe, Pedro Issao (Universidade Federal de São Carlos, 2025)
The Solvay process is the main industrial route for the production of sodium carbonate, based on the absorption of carbon dioxide by an ammoniacal solution of sodium chloride. This study provides an environmental analysis of the electrolysis process as an alternative to the Solvay process in the manufacturing of chemical compounds related to the soda ash industry. The main product of the Solvay process, sodium carbonate, serves as the foundation for essential products in various industrial sectors, such as detergent manufacturing, ceramics, paper production, the textile industry, metallurgy, soaps, petrochemicals, and water or wastewater treatment plants. However, the environmental impact of the process and its alternatives varies significantly. This study aims to compare them in terms of carbon emissions, energy efficiency, and by-product management. Despite its historical importance and widespread use, the Solvay process has been criticized for its environmental impact, and in the near future, it may need to be replaced by cleaner technologies. Meanwhile, the electrolysis process faces challenges due to the demand imbalance between caustic soda and chlorine, as both are produced simultaneously. The demand for NaOH is higher in many regions compared to Cl₂, leading to the need to find alternative applications or storage solutions for the excess chlorine produced. Through a review of articles, academic texts, and technical reports, data on carbon emissions, energy consumption, and by-products of each process were gathered. The Solvay process proved to be more energy-efficient, with consumption ranging between 2694 and 3778 kWh/ton. In contrast, electrolysis emits lower amounts of carbon, between 0.13 and 0.19 tons of CO₂ per ton, and generates fewer by-products. As a result, this study leans toward identifying electrolysis as a more sustainable alternative.
Comparative analysis of environmental impacts in the soda ash industry: electrolysis versus Solvay process
Keywords: Processo Solvay; Eletrólise; Indústria de barrilha; Impacto ambiental; Análise comparativa; Solvay process; Electrolysis; Soda ash industry; Environmental impact; Comparative analysis; ENGENHARIAS::ENGENHARIA QUIMICA